2001
DOI: 10.1016/s0960-9822(01)00424-9
|View full text |Cite
|
Sign up to set email alerts
|

Gap junction protein connexin-43 interacts directly with microtubules

Abstract: Gap junctions are specialized cell-cell junctions that mediate intercellular communication. They are composed of connexin proteins, which form transmembrane channels for small molecules [1, 2]. The C-terminal tail of connexin-43 (Cx43), the most widely expressed connexin member, has been implicated in the regulation of Cx43 channel gating by growth factors [3-5]. The Cx43 tail contains various protein interaction sites, but little is known about binding partners. To identify Cx43-interacting proteins, we perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
232
1
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 267 publications
(244 citation statements)
references
References 17 publications
8
232
1
3
Order By: Relevance
“…This motif ( 234 KGVKDRVKGK 243 , residues typically found in tubulin binding domains are underlined) is unique for Cx43 and was not found in other members of the Cx family. Consistently, specificity of tubulin binding to Cx43 was confirmed in that a microtubule interaction was not observed with C-termini of three other Cxs (Cx31.9, Cx46, Cx50) [Giepmans et al, 2001a]. The microtubule binding region in the Cx43 CT was confirmed by a similar study that demonstrated competitive binding of Cx43 with Smad2/3 to the same region on b-tubulin [Dai et al, 2007].…”
Section: A-/b-tubulinsupporting
confidence: 56%
See 4 more Smart Citations
“…This motif ( 234 KGVKDRVKGK 243 , residues typically found in tubulin binding domains are underlined) is unique for Cx43 and was not found in other members of the Cx family. Consistently, specificity of tubulin binding to Cx43 was confirmed in that a microtubule interaction was not observed with C-termini of three other Cxs (Cx31.9, Cx46, Cx50) [Giepmans et al, 2001a]. The microtubule binding region in the Cx43 CT was confirmed by a similar study that demonstrated competitive binding of Cx43 with Smad2/3 to the same region on b-tubulin [Dai et al, 2007].…”
Section: A-/b-tubulinsupporting
confidence: 56%
“…More importantly, a-and b-tubulin were found to bind to the Cx43 CT in pull-down assays using multiple cell types (see Tab. 1) [Giepmans et al, 2001a;Singh and Lampe, 2003;Butkevich et al, 2004]. A similar pull-down showed that a-tubulin and b-tubulin are equally bound [Giepmans et al, 2001b].…”
Section: A-/b-tubulinmentioning
confidence: 90%
See 3 more Smart Citations